Asian culture in transition: is it related to reported parenting styles and transitivity of simple choices?. Issue 4 (12th March 2013) - Ferguson, Eva Dreikurs; Hagaman, Joel A.; Maurer, Sarah B.; Mathews, Philip; Peng, Kaiping
Abstract Does culture shape reported parenting styles and cognitive processes like transitive reasoning, of choosing A over B, B over C, and then A over C (transitivity)? Asian‐American, Caucasian‐American, and Indian university students differed significantly in transitivity and in reported parental styles. India participants were more intransitive and, contrary to traditional findings in the literature, reported their parents as more laissez‐faire, individualistic, and competitive than did Caucasian‐Americans. Recent technological and industrial advances in India likely explain some of these obtained differences. Predictions from Adlerian theory and work of Kurt Lewin, that parenting styles would relate to transitivity of choices, were indirectly supported. Stronger evidence was found that culture impacts both reported parental styles and transitivity of simple choices.